QAS 2023
DOI: 10.47750/qas/24.192.45
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Organizational Commitment Mediates the Effect of Perceived Organizational Support and Organizational Culture on Organizational Citizenship Behavior

Abstract: The purpose of the study was to determine the extent to which the role of perceived organizational commitment mediates the influence between perceived organizational support and organizational culture on organizational citizenship behavior. Quantitative methods are used in this study. The sample used by respondents was 195 employees at a security company in Jakarta, Indonesia, with a random sampling technique. The analysis used is path analysis whose data processing is done through SmartPLS 3.0. The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…In-role performance concerns the tasks assigned to employees by their company, whereas extra-role performance refers to the roles beyond the expectations of the company. The importance of extra-role performance is evident in the literature (Williams and Anderson, 1991;MacKenzie et al, 1998;Sosik et al, 2011;Zhang et al, 2017;Sauer et al, 2023;Sumardjo and Supriadi, 2023).…”
Section: Culture and Performancementioning
confidence: 99%
“…In-role performance concerns the tasks assigned to employees by their company, whereas extra-role performance refers to the roles beyond the expectations of the company. The importance of extra-role performance is evident in the literature (Williams and Anderson, 1991;MacKenzie et al, 1998;Sosik et al, 2011;Zhang et al, 2017;Sauer et al, 2023;Sumardjo and Supriadi, 2023).…”
Section: Culture and Performancementioning
confidence: 99%
“…Örgüt kültürü çalışanların davranışları üzerinde de önemli düzeyde etkilidir ve benimsenen değerler ne kadar olumlu olursa, çalışan performansını da o ölçüde artırmaktadır (Sumardjo ve Supriadi, 2023). Endratmoko veAulia'ya (2021) göre, güçlü bir örgüt kültürü örgütsel vatandaşlık davranışının ortaya çıkmasını destekler.…”
Section: öRgüt Kültürünün Değerlendi̇ri̇lmesi̇unclassified
“…A lot of research work has been associated with supervisor support on different organizational and personal level outcomes (Ma et al ., 2023), but still few gaps have been identified (Sumardjo and Supriadi, 2023). Although, it is widely observed that supervisor support significantly impacts employee attitudinal and behavioral outcomes at the workplace the specific psychological mechanism leading this support to altruism and knowledge-sharing behavior have not been clearly established (Zhu et al ., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the current study is considering psychological well-being and psychological ownership as psychological phenomena affected by the supervisor’s support. As psychological well-being refers to an individual’s overall mental and emotional state, including their sense of purpose (McIlroy et al ., 2021), satisfaction with life (Chen and Wang, 2017) and ability to cope with stress while ownership refers to the feeling of possessing or having control over something, which can have psychological benefits such as increased sense of responsibility, identity and attachment (Ma et al ., 2023; Sumardjo and Supriadi, 2023). Whereas, altruism is the act of selflessly helping others without expecting anything in return, and knowledge sharing involves the voluntary transfer of information from one individual to another (Pohl et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation